Circadian rhythm disruption as a potential contributor to BPPV: Evidence from a young rat model vestibular effects of circadian disruption - Hüsniye Gül Otlu; Hanifi Korkmaz; Nilüfer Diller Bulut; Nurcan Göktürk (PLoS ONE, 2025)
Circadian rhythm disturbances, increasingly common due to artificial lighting and modern lifestyle factors, may underlie vestibular dysfunction such as benign paroxysmal positional vertigo (BPPV), even in younger populations. This study aimed to investigate the effects of circadian rhythm disruption on balance performance and vestibular biomarkers in a young rat model. Young male Wistar rats were exposed to constant light (CL) for 4 weeks to induce circadian disruption, while control rats were maintained under a standard 12:12-hour light–dark cycle. Following the exposure, serum and cochlear tissues were analyzed for otolin-1, vitamin D3, melatonin, and electrolytes (Ca² ⁺ , Na ⁺ , K ⁺ , Cl⁻). Balance was evaluated using the rotarod performance test. Constant light exposed rats showed significantly elevated otolin-1 levels in both serum and cochlear tissues, along with reduced melatonin levels and impaired rotarod performance. Vitamin D3 levels were lower in the CL group, while serum electrolytes remained unchanged. Circadian rhythm disruption may impair vestibular function in young rats via melatonin related pathways or otolin-1 modulation, independent of serum electrolytes. Our results imply that circadian rhythm disruption may contribute to BPPV through pathways unrelated to aging or bone metabolism.